2021
DOI: 10.1155/2021/3466813
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Operative Strategy for Secondary Mitral Regurgitation: A Systematic Review

Abstract: Background. Mitral valve disease surgery is an evolving field with multiple possible interventions. There is an increasing body of evidence regarding the optimal strategy in secondary mitral regurgitation where the pathology lies within the ventricle. We conducted a systematic review to identify the benefits and limitations of each surgical option. Methods. A systematic review of the literature was performed to identify pertinent randomized controlled trials (RCTs), propensity-matched observational series, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…In our cohort of patients with surgically repaired functional MR (of both ischemic and nonischemic etiology), we observed a recurrence of significant MR (at least grade II) in 36.9% of discharged patients after a mean follow-up of 41.8 months, data that are comparable with those of previous studies such as the 20.3% reported by Petrus et al 7) or the 32% at 3 years in ischemic MR reported by Dufendach et al 11) In recent years, the restrictive mechanism surgical technique employed for 19) report very low recurrence rates for repaired ischemic MR of around 6% at 5 years. Conversely, other reviews [8][9][10][11][12][13][14][15][16][17][18][19][20] calculate more variable rates of significant MR recurrence up to 55%-70% in all likelihood attributable to differences in the baseline characteristics of patients undergoing interventions and to the heterogeneity of surgical techniques employed, which makes it difficult to reach a consensus about a single strategy for the treatment of functional MR. Recurrence of MR after repair has a significant impact on mortality, as other studies prior to ours have shown (HR = 3.28, 95% CI = 1.87-5.75, p <0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our cohort of patients with surgically repaired functional MR (of both ischemic and nonischemic etiology), we observed a recurrence of significant MR (at least grade II) in 36.9% of discharged patients after a mean follow-up of 41.8 months, data that are comparable with those of previous studies such as the 20.3% reported by Petrus et al 7) or the 32% at 3 years in ischemic MR reported by Dufendach et al 11) In recent years, the restrictive mechanism surgical technique employed for 19) report very low recurrence rates for repaired ischemic MR of around 6% at 5 years. Conversely, other reviews [8][9][10][11][12][13][14][15][16][17][18][19][20] calculate more variable rates of significant MR recurrence up to 55%-70% in all likelihood attributable to differences in the baseline characteristics of patients undergoing interventions and to the heterogeneity of surgical techniques employed, which makes it difficult to reach a consensus about a single strategy for the treatment of functional MR. Recurrence of MR after repair has a significant impact on mortality, as other studies prior to ours have shown (HR = 3.28, 95% CI = 1.87-5.75, p <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Despite performance of repair surgery on the mitral valve, different studies report considerable heterogeneity in the high recurrence rate of MR in follow-up (ranging from 20.3% and 27.6% at 5 and 10 years, respectively, in Petrus et al 7) to rates as high as 55%-70% at 10 years. 8) ) Moreover, no significant impact on long-term survival after surgery for mitral repair in functional MR has been established. [9][10][11][12] Likewise, the majority of studies that assess the predictors of MR recurrence after repair and mortality offer discrepant results, and do not take mortality into account as a competing risk event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] The remaining two-thirds of patients with MR present with functional or secondary MR, which is characterized by the presence of regurgitation without structural changes to the leaflets. [14] The guidelines distinguish two types of functional MR. [2] Atrial MR, where atrial dilatation also affects the annulus. Here, isolated ring annuloplasty addresses the pathomechanism and should generate lasting results.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence suggests that such a replacement requires full preservation of the chordae, which is considered to preserve the often already poor left ventricular function. [ 14 , 17 , 95 , 96 ] Suggestions to quantify the restriction by measuring tenting height or area[ 14 , 82 ] or determining it by assessing angles of mitral leaflet position[ 14 , 82 ] have been made to assist in decision making for replacement. [ 73 , 82 ] The results of an Italian collaborative effort suggesting a benefit for replacement in patients with severe restriction supports this suggestion.…”
Section: Introductionmentioning
confidence: 99%